IX—A Virtue Theory of Testimony. Issue 2 (July 2014) - Faulkner, Paul
Abstract : This paper aims to outline, evaluate, and ultimately reject a virtue epistemic theory of testimony before proposing a virtue ethical theory. Trust and trustworthiness, it is proposed, are ethical virtues; and from these ethical virtues, epistemic consequences follow.